The Style of Customer Decision Making in the Bugis Community in Jambi - Karim, Kurniati; Hosen, Ahmad (Hasanuddin Economics and Business Review, 2020)
The Bugis tribe is one of the tribes that resides in South Sulawesi Province. This tribe is known to be very rational in acting and is always based on the teachings of the ancestors in the form of "Mappesona ri Dewata Seuwae" which means based on God Almighty. The Bugis tribe is known as an accomplished seaman, so they inhabit all provinces in Indonesia, including in Jambi Province. By inhabiting the Jambi area, the influence of the local culture will certainly affect the behavior of someone who resides in the area. Regarding this, the purpose of this research is to find out whether the decision making model of the Bugis people who live in Jambi still consider the Bugis cultural value when making product purchase decisions. The research sample consisted of 106 people, data were collected through questionnaires, and then analyzed descriptively quantitatively by calculating the index number values. The analysis shows that although the Bugis people have settled in Jambi, Sumatra, the product purchasing decision model is based on the value of the faith taught by the Bugis ancestors.